2021
DOI: 10.3390/s21020669
|View full text |Cite
|
Sign up to set email alerts
|

Ramie Yield Estimation Based on UAV RGB Images

Abstract: Timely and accurate crop growth monitoring and yield estimation are important for field management. The traditional sampling method used for estimation of ramie yield is destructive. Thus, this study proposed a new method for estimating ramie yield based on field phenotypic data obtained from unmanned aerial vehicle (UAV) images. A UAV platform carrying RGB cameras was employed to collect ramie canopy images during the whole growth period. The vegetation indices (VIs), plant number, and plant height were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Therefore, many researchers tend to use consumer-level sensors, but most of the previous studies were based on a single sensor data to extract plant height [ 30 , 32 ]. In this study, 2D-RGB, 2D-MS and 3D-RGB UAV imagery were collected respectively based on RGB camera and multispectral sensors, and it was found that the average plant height values of each plot extracted from these UAV imagery was lower than the ground measured values, which was consistent with the previous studies [ 48 , 49 ]. In view of the fact faba bean has branches, easy to lodging, and the plant height performance of each branch is quite different.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, many researchers tend to use consumer-level sensors, but most of the previous studies were based on a single sensor data to extract plant height [ 30 , 32 ]. In this study, 2D-RGB, 2D-MS and 3D-RGB UAV imagery were collected respectively based on RGB camera and multispectral sensors, and it was found that the average plant height values of each plot extracted from these UAV imagery was lower than the ground measured values, which was consistent with the previous studies [ 48 , 49 ]. In view of the fact faba bean has branches, easy to lodging, and the plant height performance of each branch is quite different.…”
Section: Discussionsupporting
confidence: 89%
“…These alternative methods are usually used when the fruit is hardly distinguished from the tree or increases the efficiency of the estimation. For example, the canopy projected area and canopy perimeter are correlated with the fruit load of peach trees 24 the individual crown area of the olive or almond can be used to predict yield 25 , 26 . The other one is directly counting the fruit from the tree.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation (or prediction) of the plant yield can be based on the more complex analysis of color images. Particularly, plant quantity, plant height, and color parameters (G, B, R/B, (G-B)/(R-G), VARI, and GLI) can be used as input values for multiple and stepwise regression models to estimate plant yield [146]. The application of color indices and texture parameters as input for the RFE_ELM model can be effectively used to estimate cotton yield [147].…”
Section: For Detail)mentioning
confidence: 99%